Guidelines for designing data collection and sharing systems for co-managed fisheries (FAO, 2005)
There has been an increasing shift towards co-management for which managers need to reflect on new roles and reconsider information requirements. This technical paper is in two parts and provides guidelines to help design and implement appropriate and cost-effective data collection programmes or systems. In Part 1: the Practical guide has been written specifically for co-managers and facilitators working in the field and offers simple and practical advice on helping stakeholders identify their information needs in relation to their management objectives and responsibilities, and developing collaborative ways of collecting and sharing the information in the most effective way.